Christus en die roos - Ingram, Riaan (HTS teologiese studies, 2005)
Christ and the rose Philo of Alexandria once stated the following truth: “Do you not see that to the prophet who truly desires to know and who asks what answer he is to give to those who question him concerning His name He says, ‘I am what I am,’ which is equivalent to saying, ‘It is My nature to be, not to be described by name’” (Philo Mut Nom 11-12). How does the theologian who hears God’s answer in this regard speak when others ask him or her about God? Through a discussion with Heidegger, Bultmann and Meister Eckhart, the article explores a possible answer to this question.